2018
DOI: 10.1016/j.eatbeh.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Successful weight maintainers among young adults—A ten-year prospective population study

Abstract: Only about a quarter of young adults were able to resist weight gain. Regular eating and having no history of dieting were associated with successful weight maintenance in young women and men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…A recent longitudinal observational study of persons with a mean age of 24 years showed that only a quarter of young adults maintained their body weight over 10 years, 68.3% of participants gained more than 5% of their weight and eating regularly and having no history of excessive dieting (intentionally losing ≥ 5 kg) were significant factors related to successful weight maintenance in both genders [16]. This means that continuous regular eating habits are even more essential to successful weight management.…”
Section: Discussionmentioning
confidence: 99%
“…A recent longitudinal observational study of persons with a mean age of 24 years showed that only a quarter of young adults maintained their body weight over 10 years, 68.3% of participants gained more than 5% of their weight and eating regularly and having no history of excessive dieting (intentionally losing ≥ 5 kg) were significant factors related to successful weight maintenance in both genders [16]. This means that continuous regular eating habits are even more essential to successful weight management.…”
Section: Discussionmentioning
confidence: 99%
“…To explore weight-related behaviors and their long-term health consequences in the general population, the twins were studied as individuals by adjusting correlated observations within twin pairs. Overall, weight-related ideals and behaviors appeared to have significant associations not only with weight change but also with physical and mental health in young adults over a period of 10 years (waves 4-5; Kärkkäinen et al, 2016Kärkkäinen et al, , 2018aKärkkäinen et al, , 2018b. Most young adults gained weight over 10 years.…”
Section: Weight-related Behaviorsmentioning
confidence: 94%
“…Most young adults gained weight over 10 years. Only about one out of every four young adults were able to successfully maintain his/her weight during this 10-year period (Kärkkäinen et al, 2018b).…”
Section: Weight-related Behaviorsmentioning
confidence: 98%
“…The negative consequences of overeating and substance use are diffuse and delayed in time and thus shift the weight in Equations (5) and (6) dramatically to the left. This may explain why these mental conditions are among the most difficult to treat, as the failure rates of dieting and relapse rates of substance abuse are notoriously high (Brandon and others 2007; Kärkkäinen and others 2018).…”
Section: Implications For Psychiatrymentioning
confidence: 99%